A debris-covered glacier at Kerguelen (49°S, 69°E) over the past 15 000 years. Issue 1 (February 2021) - Charton, Joanna; Jomelli, Vincent; Schimmelpfennig, Irene; Verfaillie, Deborah; Favier, Vincent; Mokadem, Fatima; Gilbert, Adrien; Brun, Fanny; Aumaître, Georges; Bourlès, Didier L.; Keddadouche, Karim
Abstract: Debris-covered glaciers constitute a large part of the world's cryosphere. However, little is known about their long-term response to multi-millennial climate variability, in particular in the Southern Hemisphere. Here, we provide first insights into the response of a debris-covered glacier to multi-millennial climate variability in the sub-Antarctic Kerguelen Archipelago, which can be compared to that of recently investigated debris-free glaciers. We focus on the Gentil Glacier and present 13 new 36 Cl cosmic-ray exposure ages from moraine boulders. The Gentil Glacier experienced at least two glacial advances: the first one during the Late Glacial (19.0–11.6 ka) at 14.3 ka and the second one during the Late Holocene at 2.6 ka. Both debris-covered and debris-free glaciers advanced broadly synchronously during the Late Glacial, most probably during the Antarctic Cold Reversal event (14.5–12.9 ka). This suggests that both glacier types at Kerguelen were sensitive to abrupt temperature changes recorded in Antarctic ice cores, associated with increased moisture. However, during the Late Holocene, the advance at 2.6 ka was not observed in other glaciers and seems to be an original feature of the debris-covered Gentil Glacier, related to either distinct dynamics or to distinct sensitivity to precipitation changes.